Todays young adult buying behaviour: the practical effect from social influencers - Ayob, Nor Azira; Aziz, Mohd Amar; Ayob, Noor Hadzlida; Kamarudin, Nurul Aqilah; Mohd Zaidi, Muhammad Zarul; Aziz, Nur Amalina; Mustapha, Siti Zulaikha (Faculty of Administrative Science and Policy Studies, 2024)
Recently, Social media has been a trending topic which are frequently discussed by the researchers. People love to use social media frequently for acquiring gratification and satisfaction in their daily life. Influencer marketing has evolved into one of the most effective techniques for reaching out to new audiences through social media. There has been growing concern about the trustworthiness of influencer marketing. The stakeholder of the marketing manager must extinguish which influencers could reach new consumers for their branding. Therefore, the number of social media followers that plays its roles as stakeholder assumes the more the followers the highest potential customer, they will gain. Due to that notion, many people want to grab that opportunity by obtaining fake followers on social media platforms. This fraudulent action might harm the influencer marketing and customers due to trustworthy issues. As a result, the study's purpose is to look into how social effects affect young adults' purchase decisions. The questionnaire is used as a tool for gathering data. The objectives of this study is to examine the factors, such as source legitimacy, source attractiveness, and fit between social influencer and product endorsement, that affect young adults' purchasing decisions in Malaysia. To gather primary data, a sample of 388 respondents among the young adult were distributed survey questionnaires. In observing the independent variables of the study (source credibility, source of attractiveness and the fit between social influencer and product endorsement) Pearson Correlation Coefficient and Multiple Linear Regression Analysis is conducted. All of these elements have a significant impact on young adults' shopping behaviour.